Low risk of ischemic stroke in patients with reduced internal carotid artery lumen diameter distal to severe symptomatic carotid stenosis: cerebral protection due to low poststenotic flow? On behalf of the European Carotid Surgery Trialists' Collaborative Group. - Rothwell, P; Warlow, C (2000)
BACKGROUND AND PURPOSE: Patients with recently symptomatic severe carotid stenosis have a high risk of ischemic stroke on medical treatment. The main mechanism of stroke appears to be plaque surface thrombus formation and distal embolism. It is unclear to what extent reduction in blood flow across the stenosis, and the consequent reduction in cerebral perfusion pressure, is also important. Angiographic indices of reduced cerebral perfusion may identify patients at a particularly high risk of stroke who require urgent endarterectomy. The most direct angiographic correlate of poststenotic perfusion pressure is the degree of narrowing of the distal internal carotid artery (ICA) lumen. We sought to develop criteria for the definition of poststenotic narrowing of the ICA and to determine the effect of this and other angiographic characteristics likely to be associated with reduced cerebral perfusion on the risk of ipsilateral ischemic stroke in patients with recently symptomatic carotid stenosis. METHODS: We studied the carotid angiograms of 3007 patients in the European Carotid Surgery Trial. Poststenotic narrowing of the ICA was defined with use of the ratio of the lumen diameter of the ICA to that of the common carotid artery (CCA). The normal range of the ICA/CCA ratio was defined in 2966 symptomatic or contralateral carotid arteries with 0% to 49% stenosis. Arteries with 70% to 99% symptomatic stenosis and an ICA/CCA ratio below this range were categorized as narrowed. We related the presence of narrowing and other angiographic characteristics to the risk of ipsilateral ischemic stroke on medical treatment. RESULTS: An assessment of the ICA/CCA ratio had good interobserver reproducibility. Poststenotic narrowing of the ICA was defined as an ICA/CCA ratio of <0.42. The 5-year risk of ipsilateral carotid territory ischemic stroke on medical treatment was 8% in patients with 70% to 99% stenosis and narrowing of the ICA versus 25% in patients without narrowing (log rank test, P=0.02). This difference remained after correction for other clinical and angiographic variables (hazard ratio 0.40, 95% CI 0.17 to 0.94, P=0. 03). The other angiographic characteristics did not predict stroke. CONCLUSIONS: Poststenotic narrowing of the ICA was associated with a low risk of stroke on medical treatment. This suggests that low flow alone is not usually sufficient to cause ischemic stroke distal to symptomatic carotid stenosis. Poststenotic narrowing may be protective because blood flow distal to the stenosis is insufficient to carry emboli to the brain.